PENGARUH DAYA TARIK IKLAN DAN INFLUENCER MARKETINGTERHADAP KEPUTUSAN PEMBELIAN PRODUK BUSANA MUSLIM BUTTONSCARVES DENGAN ONLINE CUSTOMER REVIEWS SEBAGAI MODERASI (STUDI KASUS KOTA YOGYAKARTA, KABUPATEN BANTUL DAN KABUPATEN SLEMAN): PENGARUH DAYA TARIK IKLAN DAN INFLUENCER MARKETINGTERHADAP KEPUTUSAN PEMBELIAN PRODUK BUSANA MUSLIM BUTTONSCARVES DENGAN ONLINE CUSTOMER REVIEWS SEBAGAI MODERASI (STUDI KASUS KOTA YOGYAKARTA, KABUPATEN BANTUL DAN KABUPATEN SLEMAN) - aini, Aini Fransisca; Syarif As’ad (ITB AAS INDONESIA Surakarta, 2025)
The study aims at learning the effect of advertisement and influencer marketing on the purchase decision of Buttonscarves muslim fashion products with online customer review as the moderation (a study case in Yogyakarta City and Bantul and Sleman districts). The survey method was quantitative, employing questionnaires to collect the data from 100 respondents. The data were analysed using the Partial Least Squares – Structural Equation Model (PLS-SEM) through Smartpls v. 4. 1. 0. 9 software. The result indicated that advertisement and influencer marketing affected the purchase decision positively and significantly. The message and visual elements in advertisement are the main factors that attract the consumer’s interest. Meanwhile, the credible influencer marketing recommendation increased confidence and boosted purchases. However, it did not moderate the relationship between advertisement and purchase decision, indicating that consumers were affected more by the visual aspects than customer reviews. On the other hand, online customer reviews moderated the effect of influencer marketing on the purchase decision, where the positive reviews strengthened the credibility of influencer marketing and increased the customer’s confidence.Keywords: Advertisement, Influencer Marketing, Marketing, Online Customer Reviews, Purchase Decision, Muslim Outfit